1980
DOI: 10.1111/j.1365-2133.1980.tb08152.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pacinian neurofibroma and relationship with the finger-tip arterio-venous anastomoses

Abstract: Multiple Pacinian neurofibromas involving the three phalanges of the ring finger of the left hand in a 60-year-old woman are described. The abnormal proliferation of Vater-Pacini corpuscles in various stages of differentiation was associated with marked changes of the glomus type of arterio-venous anastomoses of the finger-tip. The close relationship between the new proliferated Vater-Pacini corpuscles, their altered baresthetic function and the pathological shunting of blood account for the painful Raynaud-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Pacinian neurofibromas are usually seen in solitary forms but McCormack et al came across multiple tumours of buttocks [8] and Levi and Curi have also reported multiple neurofibromas of fingers in form of pacinian neurofibromatosis [9]. These benign tumours usually lack cellular pleomorphism and mitotic figures but King and Barr reported a case of pacinian neurofibroma with cellular pleomorphism and mitotic figures and proposed a new term for such forms as 'bizarre cutaneous neurofibromas' [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pacinian neurofibromas are usually seen in solitary forms but McCormack et al came across multiple tumours of buttocks [8] and Levi and Curi have also reported multiple neurofibromas of fingers in form of pacinian neurofibromatosis [9]. These benign tumours usually lack cellular pleomorphism and mitotic figures but King and Barr reported a case of pacinian neurofibroma with cellular pleomorphism and mitotic figures and proposed a new term for such forms as 'bizarre cutaneous neurofibromas' [10].…”
Section: Discussionmentioning
confidence: 99%
“…[1] It usually occurs as a solitary nodule, most often on the hands and feet, where Pacinian corpuscles are usually concentrated. [2,3] Lesions may occur elsewhere also. [1,2] Diagnosis is established by histopathology features, which may be variable.…”
mentioning
confidence: 96%
“…[2,3] Lesions may occur elsewhere also. [1,2] Diagnosis is established by histopathology features, which may be variable. We report a case of PN which presented as a slowly growing tumor on the forearms.A 17-year-old boy presented with an asymptomatic, well-defined, irregular, sessile, slow-growing tumor [ Figure 1] on the extensor aspect of right forearm of 3 years duration.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Pacinian corpuscle neuromas may be associated with other lesions such as glomus tumour, Dupuytren's contracture, multiple Pacinian neuroma and arteriovenous anastomoses (14)(15)(16).…”
Section: Review Of Literaturementioning
confidence: 99%